2022
DOI: 10.1021/acs.langmuir.2c02672
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Magnetic ZIF-90 Nanoparticles Improves the Microenvironment of Immobilized Lipase and Its Application in Esterification

Abstract: Interactions of enzymes with supports significantly affect the activity and stability of immobilized enzymes. Herein, amino-functionalized ionic liquid (IL)-grafted magnetic zeolitic imidazolate framework-90 (MZIF-90) was prepared and used to immobilize porcine pancreatic lipase (PPL). The nanocomposites were fully characterized; meanwhile, the interactions between ILs and ZIF-90 were calculated based on density functional theory. The prepared biocatalyst (PPL-ILs/MZIF-90) had a lipase loading of 178.3 mg/g an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Most recently, our team investigated IL-modified MOF (IL-NH 2 -MIL-101) for laccase immobilization, which confirmed that immobilized enzymes exhibited improved stability and activity, and achieved efficient pollutant degradation rates [17]. Moreover, Suo et al [18] developed amino-functionalized IL-grafted magnetic MOF (ZIF-90) for the immobilization of porcine pancreatic lipase (PPL-ILs/MZIF-90), which demonstrated the high esterification efficiency of synthetic isoamyl acetate. The introduction of IL enhances the binding between the enzyme and the carrier, improves the flexibility of the carrier on the surface of the enzyme, and further alters the structural conformation of the lipase.…”
Section: Introductionmentioning
confidence: 85%
“…Most recently, our team investigated IL-modified MOF (IL-NH 2 -MIL-101) for laccase immobilization, which confirmed that immobilized enzymes exhibited improved stability and activity, and achieved efficient pollutant degradation rates [17]. Moreover, Suo et al [18] developed amino-functionalized IL-grafted magnetic MOF (ZIF-90) for the immobilization of porcine pancreatic lipase (PPL-ILs/MZIF-90), which demonstrated the high esterification efficiency of synthetic isoamyl acetate. The introduction of IL enhances the binding between the enzyme and the carrier, improves the flexibility of the carrier on the surface of the enzyme, and further alters the structural conformation of the lipase.…”
Section: Introductionmentioning
confidence: 85%
“…At pH 6.5, PPL-ILs/MCaBDC showed a residual activity of 63.4% which was higher than that of PPL immobilized on IL modified MZIF-90 (51.6%) as reported. 50 This phenomenon indicated that PPL-ILs/MCaBDC was more stable under acidic conditions because of the good stability of CaBDC-MOF at acidic pH. 51 Fig.…”
Section: Activity and Stability Assessmentmentioning
confidence: 96%